Responses of tree seedlings to understory filtering by the recalcitrant fern layer in a subtropical forest - Liu, Heming; Liang, Mengfang; Yang, Qingsong; Zhang, Jian; Shen, Guochun; Zhang, Zhenzhen; Wang, Xihua (Frontiers in Plant Science, 2022)
The recalcitrant understory fern layer is an important ecological filter for seedling regeneration, yet how the fern layer influences seedling regeneration dynamics remains unclear. Here we transplanted 576 seedlings of four dominant tree species, Castanopsis fargesii, Lithocarpus glaber, Schima superba and Hovenia acerba, to the treatments of Diplopterygium glaucum retention and removal under an evergreen broad-leaved forest in eastern China. We monitored the survival, growth and biomass data of these seedlings for 28 months, and then used generalized linear mixed models to evaluate the treatment effects on seedling survival, growth, biomass and root-shoot ratio. Our results showed that fern retention significantly inhibited the seedling establishment of all four species. During the seedling development stage, the seedling relative growth rate of L. glaber decreased under fern retention, which was not the case for the other three species. Root-shoot ratio of C. fargesii and L. glaber increased significantly under fern retention. Our findings provide new evidence of the filtering effect of a recalcitrant fern understory. Notably, we observed that the response of tree seedlings to the recalcitrant fern understory was more sensitive in the establishment stage. Finally, our work highlights that the filtering effect of the recalcitrant fern understory changes depending on the regeneration stages, and that shade-tolerant species, C. fargesii and L. glaber were even more affected by fern disturbed habitats, suggesting that effective management should attempt to curb forest fern outbreaks, thus unblocking forest recruitment.